Defining the role of post-translational modification on the mismatch repair and meiotic crossover protein Mlh1 - Fairbanks, Harriet (2023)
Accurate cell division is essential for the longevity of all species. Meiosis is a specialised cell division that generates four genetically distinct haploid gametes through a process called crossover formation followed by two sequential cellular divisions. Crossovers can be divided into two main groups, interfering and non-interfering crossovers, the former of which is catalysed by the protein Mlh1-Mlh3, through the bias resolution of double Holliday junctions (dHJs). Mlh1 is involved in meiotic recombination, mismatch repair (MMR) and gene tract length control, with several phosphodegron sites, S135, S431, S439 and S441 identified by Swaney et al. (2013) and Lanz et al. (2021). Different phosphomimetic and phosphomutant combinations of these sites were generated and it was hypothesised that more phosphomutant sites would cause Mlh1 abundance to increase and crossover (CO) frequency to increase, while more phosphomimetic sites would cause Mlh1 abundance to decrease and CO frequency to decrease. In this study it was identified that the linker region of Mlh1 is essential for CO regulation and every mutation characterised resulted in an increase in CO frequency, possibly due to compensation by another endonuclease. Phosphorylation of the analysed phosphodegron sites is essential for accurate chromosomal segregation, spore viability and sporulation efficiency, but its effect on CO frequency could not be determined. This has established further avenues of research such as investigating specific extension of the linker region, identifying the kinase involved, and comprehensive analysis using long read next generation sequencing (NGS).